2015
DOI: 10.1262/jrd.2014-106
|View full text |Cite
|
Sign up to set email alerts
|

Let-7-mediated suppression of mucin 1 expression in the mouse uterus during embryo implantation

Abstract: Mucin 1 (Muc1) is an integral transmembrane mucin glycoprotein expressed on the apical surface of most epithelia. It is considered to be a barrier to the regulation of embryo implantation by inhibiting attachment of the embryo to the endometrium. Therefore, loss of Muc1 on the surface of uterine epithelial cells is necessary for embryo implantation. Studies have demonstrated that microRNAs (miRNAs) play a key role in enhancing embryo implantation in mammals. In this study, we investigated the regulatory role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Previous studies have demonstrated that direct interaction of Let-7a with the 3′-untranslated region (3′-UTR) of Muc-1 is possible. Moreover, Let-7a can mediate Muc-1 expression (Inyawilert, Fu, Lin, & Tang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that direct interaction of Let-7a with the 3′-untranslated region (3′-UTR) of Muc-1 is possible. Moreover, Let-7a can mediate Muc-1 expression (Inyawilert, Fu, Lin, & Tang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mmu-let-7b-3p has also been shown to mediate the epithelial innate immune response via TLR signalling (Hu et al, 2009). Furthermore, let-7b is also known to target Tlr4 and regulates the activation of NF-κB and the expression of downstream genes related to immune responses in Helicobacter pylori infection (Teng et al, 2013) while also binding to the Muc1 gene in epithelial cells (Inyawilert et al, 2015). miR-141-3p is expressed in immune cells (natural killer cells, leukocytes) and both inflamed and noninflamed epithelial cells in the small and large intestine (Lee et al, 2015).…”
Section: Please Cite This Article As 'In Press'mentioning
confidence: 99%
“…The high levels of let‐7 in the receptive uterus could be important for differentiation of a receptive endometrium. One of the targets of let‐7a and let‐7b is Muc1 , which encodes mucin that blocks embryo attachment in many species . In mice, the expression of MUC1 is abundant in the non‐receptive uteri but is greatly reduced in the luminal epithelium in the WOI .…”
Section: Mirnas In Endometriummentioning
confidence: 99%